Shaking up the schoolhouse : how to support and sustain educational innovation - Schlechty, Phillip C. (San Francisco : Jossey-Bass, 2001)
Drawing from many years of experience and from actual cases, the author describes the essential characteristics of change-adept organizations. He then presents a practical framework for helping teachers to overcome obstacles in the learning experience, from reviewing the competition to improving student engagement through more effective standards.
Includes bibliographical references and index.
Keywords: School improvement programs -- United States; Curriculum change -- United States